2002
DOI: 10.1081/css-120014544
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Occurrence of Atrazine, Deethylatrazine, and Ametryne Residues in Groundwater of the Tropical Island Barbados

Abstract: The triazine herbicides atrazine (AT) and ametryne (AMET) are used extensively in Barbados to control weeds in sugar cane fields. These pesticides were monitored in groundwater (the primary source of potable water on the island) for the dry seasons July -December, 1992. Residues of either AT or AMET were detected in all 277 groundwater samples collected from 23 wells in three major groundwater catchments underlying heavily cultivated sugar cane fields. The concentration of AT and the metabolite deethylatrazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Indeed, monitoring programs across tropical Australia, Brazil, Chile, Barbados, and Hawaii have detected several relatively polar pesticides in rainwater, surface runoff, and groundwater. These include PSII-inhibiting herbicides (diuron, metribuzin, simazine, atrazine, tebuthiuron, and hexazinone), the chloroacetanilide herbicide metolachlor, the auxin growth regulator 2,4-D, and the neonicotinoid insecticide imidacloprid at concentrations that may pose environmental or human-health risks. , , Furthermore, the highly volatile endosulfan continues to be an issue in Brazil. , Indeed, lessons from temperate environments highlight that where pre-emergent, soil-applied pesticides (such as those listed here) are used in large amounts, their off-site migration may be an issue, as they are often highly prone to runoff …”
Section: Environmental Risk Of Pesticides In Tropical Environmentsmentioning
confidence: 99%
“…Indeed, monitoring programs across tropical Australia, Brazil, Chile, Barbados, and Hawaii have detected several relatively polar pesticides in rainwater, surface runoff, and groundwater. These include PSII-inhibiting herbicides (diuron, metribuzin, simazine, atrazine, tebuthiuron, and hexazinone), the chloroacetanilide herbicide metolachlor, the auxin growth regulator 2,4-D, and the neonicotinoid insecticide imidacloprid at concentrations that may pose environmental or human-health risks. , , Furthermore, the highly volatile endosulfan continues to be an issue in Brazil. , Indeed, lessons from temperate environments highlight that where pre-emergent, soil-applied pesticides (such as those listed here) are used in large amounts, their off-site migration may be an issue, as they are often highly prone to runoff …”
Section: Environmental Risk Of Pesticides In Tropical Environmentsmentioning
confidence: 99%
“…Although these levels in general were higher than those reported in the literature, lower application rates of atrazine should be considered to preserve the quality of potable water on the island (Wood et al, 2002a). Tappe et al (2002) reported that atrazine was the most frequently applied herbicide in cultivated areas of Germany until it was prohibited in 1991.…”
Section: Xenobiotics Atrazinementioning
confidence: 92%